Health Promoting Hospitals Model in Iran - Maryam YAGHOUBI (Iranian Journal of Public Health, 2016)
Background: Hospitals are the central entity of each health care system and Health Promoting Hospitals (HPH) was launched by WHO in 1988. However, there has not been any accurate and detailed model for establishing a HPH in Iran up to now. Therefore, this study aimed to determine factors affecting the establishment of a health promoting hospital in Iran using factor analysis method.